Ultra Groups as Social Space for Leisure - Seabra Daniel (Sciendo, 2017)
The paper aims to demonstrate that violence is far from a regular practice in Ultra groups, despite its notorious visibility as transmitted by the media. The paper attempts to demonstrate that Ultra groups are a social space of leisure for young people, rather than a space for violence. Actually, having used observation through direct participation and having registered the discourses of Ultra group members, it is possible to demonstrate that life in these groups represents, for many, not only a break from difficult everyday life, but also the only and/or the most important moment of social leisure in their lives.